ModifiedCritical Incident (mCIT): AMeans to Uncover Experience of Mobile Social Messaging System Using Informant-SpecificCues - et.al, FazillahMohmad Kamal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Part of Human-computer interaction (HCI)researchevolves around understanding of the experiential aspects of users -their what, why and how of technology use in the domestic setting which is always privy to the users. The process of understanding is often not straightforward and a reliable means to develop thisHCI knowledge is deemed necessary. This article describes a study whereCritical Incident Technique (CIT) was adapted to HCI research and applied in the context of social messaging system use in understanding technology-mediated familial bonding enactment.CIT often involves the recalled critical incidents – or significant instances of a specific activity as experienced by research participants to recognize similarities, differences, and patterns, and to seek insights into how and why people engage in the activity of interest.However, such approach may contaminate the reliability and trustworthiness of the findings. Thus, our adapted version of CIT utilizes the procedures and logic of CIT, but differs in two ways: 1) Relying on situated and informants’ genuine critical incidents to elicit experience of interaction and 2) ‘uncritical’ incidents were also included as complementary to critical incidents to cueing informants on the phenomenon of interest. This uncritical incident represents negative evidence to counter the drawback of existing technique.Considering both critical and uncritical incidents in the studyhas provided a bigger picture and rich descriptions of the technology-mediated familialbonding enactment from both lens ofgenuine incidents and informants.